1998
DOI: 10.1046/j.1365-2796.1998.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Raised platelet levels in diabetes mellitus complicated with nephropathy

Abstract: Abstract. Sterner G, Carlson J, Ekberg G (Malmö University Hospital, Malmö, Sweden). Raised platelet levels in diabetes mellitus complicated with nephropathy. J Intern Med 1998; 244: 437-41.Objectives. To study if elevated platelet levels are found in early and late diabetic nephropathy. Design. A retrospective study was performed of platelet count in different subgroups of patients with insulindependent diabetes mellitus, including patients with long and short duration of diabetes and with early signs of neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 1 publication
2
9
1
1
Order By: Relevance
“…A higher platelet count could contribute to the formation of microthrombi and affect renal microcirculation. Sterner et al [20] have shown a significantly raised platelet count in type 1 diabetic patients with nephropathy, but this has not been previously reported in type 2 diabetes. It has been suggested that both the total number of platelets and their ability to aggregate could influence the microvascular circulation in DM and play a part in the progression of arteriosclerotic lesions [21].…”
Section: Discussionmentioning
confidence: 77%
“…A higher platelet count could contribute to the formation of microthrombi and affect renal microcirculation. Sterner et al [20] have shown a significantly raised platelet count in type 1 diabetic patients with nephropathy, but this has not been previously reported in type 2 diabetes. It has been suggested that both the total number of platelets and their ability to aggregate could influence the microvascular circulation in DM and play a part in the progression of arteriosclerotic lesions [21].…”
Section: Discussionmentioning
confidence: 77%
“…Platelets in T2DM are characterized by dysregulation of several signaling pathways, and they can become hyperreactive and more prone to undesirable activation, adhesion, and aggregation (6)(7)(8)(9). Other abnormalities such as raised platelet count and high mean platelet volume (MPV) have also been observed in T2DM (10,11). Shilpi et al (12) showed that MPV (11.3 5 1.0 fL) in diabetics is significantly higher than the MPV (9.0 5 0.6 fL) in nondiabetics.…”
Section: Introductionmentioning
confidence: 99%
“…Sterner et al, observed a connection between raised platelet number and diabetic female gender. He also noted that diabetic nephropathy is related to platelet count and function, so platelet count might be a future prognostic indicator for diabetic complications, opening new study directions [11]. The indirect corelation between mean platelet volume and diabetes duration was not what we expected, since larger platelets are thought to be more active and thrombogenic than normal or smaller ones.…”
Section: Resultsmentioning
confidence: 72%